Intelligent operation and maintenance of power communication network based on data perception fusion - Huahui LYU; Zhe MING; Kai FAN; Qingming CHEN; Hongyu SHI; Wenjing ZOU; Dingbo WANG; Shengtao GUAN; Yong WU (Dianxin kexue)
Under the common influence of multiple factors and structural complexity in the power communication network, traditional operation and maintenance methods are vulnerable to the disturbance of abnormal voltage signal and abnormal transformer signal in the perception process, resulting in the global perception of the network and seriously affecting the overall operation and maintenance effect.In order to effectively solve the problem of perception bias caused by multiple factors, the data perception fusion algorithm was used to optimize the perception of the power parameters under the power communication network, so as to realize the effect of improving the perception accuracy and optimizing the overall quality of operation and maintenance.In the optimization scheme, the situational awareness scope of power communication network security was determined firstly.Secondly, the situational awareness of voltage security under power communication network operation was optimized.Thirdly, the security situational awareness parameters of power network transformer were defined based on the data perception fusion algorithm.Finally, the data perception fusion calculation of perception information was completed.The simulation comparison test shows that the data perception fusion algorithm has the ability to improve the overall quality of operation and maintenance, reduce the perception deviation in the process of operation and maintenance, and improve the perception sensitivity and accuracy.